Goosebumps : creepy creatures - Stine, R. L.; Stine, R. L.; Stine, R. L.; Hernandez, Gabriel (Hernandez Walta).; Ruth, Greg.; Morse, Scott (New York : Graphix, 2006)
"3 goulish graphix tales"--Cover.
The werewolf of Fever Swamp / adapted & illustrated by Gabriel Hernandez -- The scarecrow walks at midnight / adapted & illustrated by Greg Ruth -- The abominable snowman of Pasadena / adapted & illustrated by Scott Morse.
Keywords: Horror stories; Cartoons and comics; Graphic novels; Graphic novels